Edukasi Gizi untuk pencegahan Stunting pada balita di Desa Marente Kab. Sumbawa - Hamdin Hamdin; Abdul Hamid; Nur Arifatus Sholihah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Stunting is a nutritional problem caused by prolonged nutritional deficiencies during the critical first 1,000 days of life (HPK). This results in growth disorders in children, resulting in a lower height or shorter stature (dwarfism) than the standard for their age. Objective: To provide information to parents of toddlers about the dangers and impacts of stunting. Nutrition education is one of the main strategies in stunting prevention by providing the community with an understanding of the importance of a healthy diet. This education includes: the importance of exclusive breastfeeding for the first 6 months and the provision of appropriate complementary foods (MPASI), the introduction of balanced nutritious foods, especially animal protein, which supports child growth, and good hygiene practices, such as washing hands before eating and maintaining environmental sanitation. The activity was carried out by providing education on stunting prevention to parents of toddlers through outreach in Marente Village, Alas District, Sumbawa Regency. The media used in this activity were leaflets distributed to parents of toddlers. Parental knowledge after receiving the educational materials provided. Parental knowledge increased, a significant increase. Before education, only 25.0% of parents had high knowledge about stunting, while after education, this increased to 77.5%.